Sodium solid electrolyte material and preparation method and application thereof

By doping rare earth sodium silicate solid electrolyte, a high-performance Na5 type sodium solid electrolyte is formed, which solves the problems of low conductivity and complex process in sodium ion batteries, and achieves the improvement of high energy density and safety.

CN119275335APending Publication Date: 2025-01-07SUN YAT SEN UNIVERSITY SHENZHEN +1
View PDF 0 Cites 1 Cited by

Patent Information

Application Number
CN202411617185.0
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-11-13
Publication Date
2025-01-07

AI Technical Summary

Technical Problem

The solid electrolyte materials in existing sodium ion batteries have poor cycle stability and poor rate performance, and are complex in preparation process and high sintering temperature, which leads to high costs and safety hazards.

Method used

By doping the rare earth sodium silicate solid electrolyte, the non-integer ratio and boron doping amount of rare earth elements are adjusted to form a pure Na5-type sodium solid electrolyte, reducing the sintering temperature and improving the room temperature ion conductivity.

Benefits of technology

The preparation of sodium solid electrolyte materials with high ionic conductivity is achieved, the process flow is simplified, the cost is reduced, and the energy density and safety of sodium ion batteries are improved.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119275335A_ABST
    Figure CN119275335A_ABST
Patent Text Reader

Abstract

The invention relates to a sodium solid electrolyte material and a preparation method and application thereof, and belongs to the technical field of solid electrolyte. The chemical formula of the sodium solid electrolyte material is Na < 5 + 3x-y > R < 1-x > PySi < 4-y > O12, R is at least one of Tm, Ho, Nd, Ce and La, x and y meet the conditions that x is larger than or equal to 0 and smaller than 0.4, y is larger than 0 and smaller than 0.8, and the sodium solid electrolyte can form a Na5 type rare earth sodium silicate structure with high ionic conductivity. And the preparation process is simple, and the method has the advantages of low sintering temperature, easily available raw materials, low cost, easy industrial mass production and the like.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to the technical field of solid electrolytes, and in particular to a sodium solid electrolyte material and a preparation method and application thereof. Background Art

[0002] In recent years, with the widespread use of renewable energy and the rapid development of the electric vehicle market, society's demand for high-performance energy storage systems has increased significantly. In current research and applications, lithium-ion batteries have attracted much attention due to their excellent electrochemical properties. However, the low reserves of lithium resources on the earth have limited their continued development in the future to a certain extent. The electrochemical properties of sodium are similar to those of lithium, and its natural abundance is more than a thousand times that of lithium, and its price is lower. Therefore, sodium-ion batteries are considered to be a more sustainable and economical alternative in the field of energy storage.

[0003] Currently, commercial sodium-ion batteries often use a combination of organic liquid electrolytes and separators. This system has safety hazards such as flammability, leakage, and short circuit caused by sodium dendrite growth. Therefore, assembling all-solid-state batteries based on non-flammable solid electrolytes with good mechanical strength is considered to be one of the important directions for the development of future energy storage technology. Currently, there are few types of sodium solid-state sodium electrolytes that have been deeply studied, and the prepared solid-state sodium-ion batteries have problems such as poor cycle stability and poor rate performance.

[0004] Exploring high-performance sodium ion solid electrolytes is conducive to improving the energy density and overall safety of sodium ion batteries, laying a solid foundation for the further development of sodium ion battery technology. In the past, sodium ion oxide solid electrolytes with high ionic conductivity, such as NaSICON and β / β”-Al 2 O 3 There are problems such as high sintering temperature (requires sintering at high temperatures of 1200°C and 1600°C respectively) and complex preparation process (Chemical Reviews, 2011, 111(5), 3577-3613). Exploring solid electrolyte materials with low sintering temperature and simple process is conducive to reducing the overall preparation cost. In addition to the above two oxide solid electrolyte materials, Na5-type rare earth sodium silicate material Na 5 R 4 O 12 (R is a rare earth element) was also found to have good sodium ion conductivity and can be synthesized below 1150°C. However, in the early days, this solid electrolyte material was often prepared by melt cooling glass ceramics, which was a complex process and had a high ionic conductivity Na5 phase (Na 5 R 4 O 12 ) is usually accompanied by the formation of a low ionic conductivity Na3 phase (Na 3R 3 O 9 ) and Na9 phase (Na 9 R 6 O 18 ), resulting in a lower overall ionic conductivity of the material.

[0005] Therefore, the development of pure Na5 phase with high ionic conductivity, simple preparation process and low cost sodium ion solid electrolyte is of great significance for the application of high-performance sodium ion solid-state battery technology. Summary of the invention

[0006] The purpose of the present invention is to overcome the shortcomings of the prior art and provide a sodium solid electrolyte material and a preparation method and application thereof. The present invention obtains a pure Na5-type sodium solid electrolyte by doping a rare earth sodium silicate solid electrolyte, which significantly improves the room temperature ionic conductivity, and has a simple preparation process, a low sintering temperature, and is easy to industrialize and mass produce.

[0007] To achieve the above object, the technical solution adopted by the present invention is:

[0008] In a first aspect, the present invention provides a sodium solid electrolyte material, wherein the sodium solid electrolyte material is Na 5+3x-y R 1-x P y Si 4-y O 12 , wherein R is at least one of Tm, Ho, Nd, Ce, and La, 0≤x<0.4, 0<z<0.8.

[0009] Rare earth sodium silicate ceramic-based solid electrolyte is composed of RO 6 The near planes of the octahedrons connected together [Si 12 O 36 ] 24- The rings form a 3D framework, and Na ion channels are formed between the rings. 12 O 36 ] 24- The atoms of the ring, their radius and atomic occupancy rate greatly affect the phase interval of Na3, Na5, and Na9 phases and the size of the Na ion channel. 5 R 4 O 12 , while adjusting the non-stoichiometric ratio of the R element and doping the Si site, jointly adjusting the Na ion concentration and channel size in the lattice, can promote the Na5 phase (Na 5 R 4 O 12) is formed, which significantly improves the ionic conductivity, thereby improving the performance of the solid electrolyte. In addition, the incorporation of P elements also increases the density of the ceramic electrolyte, reduces the sintering temperature and improves the ionic conductivity of the material.

[0010] In the chemical formula of the present invention: R is a rare earth element with a valence state of +3, x reflects the content of the R element, which will affect the non-stoichiometric ratio of R atoms in the material lattice; the P element dopes the Si position, and y reflects the doping amount of the P element. When the P element is not doped and the R ratio is too low, the Na9 impurity phase will be generated and the conductivity will be significantly reduced; while excessive doping of the P element will lead to the generation of the Na3 impurity phase, and the conductivity will also be significantly reduced. Under the doping amount specified in the present invention, a Na5-type sodium solid electrolyte material can be formed, achieving a significant improvement in ionic conductivity.

[0011] The present invention uses doping modification to make the synthesized solid electrolyte have a Na5-type structure without obvious impurities, thereby achieving high ionic conductivity, and to reduce the sintering temperature. The prepared sodium solid electrolyte has an ionic conductivity of more than 1 mS / cm at room temperature.

[0012] Preferably, R is Ho or Nd.

[0013] Preferably, 0≤x≤0.3, 0<y≤0.5.

[0014] In the above preferred element doping amount range, the conductivity of the sodium solid electrolyte material is compared with the undoped Na 5 R 4 O 12 Significant improvement.

[0015] As a preferred embodiment, the sodium solid electrolyte material is Na 5.5 Ho 0.7 P 0.4 Si 3.6 O 12 、Na 5.3 Ho 0.8 P 0.3 Si 3.7 O 12 、Na 5.25 Ho 0.85 P 0.2 Si 3.8 O 12 、Na 5.2 Ho 0.9 P 0.1 Si 3.9 O 12 、Na 5.1 Ho 0.95 P 0.05 Si 3.95 O12 、Na 5.4 Nd 0.7 P 0.5 Si 3.5 O 12 One of them.

[0016] When the sodium solid electrolyte material is Na 5.25 Ho 0.85 P 0.2 Si 3.8 O 12 When the ionic conductivity is significantly increased to 2.2×10 -3 S / cm, solid electrolyte material is Na 5.4 Nd 0.7 P 0.5 Si 3.5 O 12 , its conductivity reaches 2.5×10 -3 S / cm. It should be noted that the scheme of the sodium solid electrolyte material of the present invention is not limited to the above-mentioned specific ones, and those skilled in the art can adjust or replace the doping elements and doping ratios within the limited range of the sodium solid electrolyte material of the present invention according to actual needs.

[0017] Preferably, the electrical conductivity of the sodium solid electrolyte material is ≥1 mS / cm.

[0018] Further preferably, the conductivity of the sodium solid electrolyte material is 10 -3 -10 -2 S / cm.

[0019] In a second aspect, the present invention provides a method for preparing the above-mentioned sodium solid electrolyte material, comprising the following steps:

[0020] (1) ball milling and mixing a Na source, an R source, a Si source, and a P source to obtain a raw material mixture;

[0021] (2) sintering the raw material mixture once to obtain a precursor powder;

[0022] (3) performing secondary ball milling and tableting on the precursor powder to obtain an electrolyte green body;

[0023] (4) performing secondary sintering on the electrolyte green body to obtain the sodium solid electrolyte material.

[0024] Preferably, the rotation speed of the primary ball milling and the secondary ball milling is 200-800 rpm, and the time is 0.5-24 h.

[0025] Preferably, in the step (1), the mixture is ball-milled and mixed once before drying; the drying temperature is 50-100° C., and the drying time is 1-24 h.

[0026] Preferably, in step (2), the primary sintering temperature is 600-950° C., and the pre-sintering time is 1-24 h.

[0027] Preferably, in step (3), the tabletting pressure is 2-15 tons.

[0028] Preferably, in step (4), the secondary sintering temperature is 900-1150° C., and the sintering time is 1-48 hours.

[0029] Introducing P source into the raw materials can lower the densification sintering temperature required by the method and reduce the preparation cost.

[0030] Preferably, the Na source and R source are at least one of oxides, hydroxides and carbonates of Na and R, respectively;

[0031] Preferably, the Si source is silicon dioxide, and the P source is at least one of phosphorus pentoxide, ammonium dihydrogen phosphate, ammonium hydrogen phosphate, and ammonium phosphate;

[0032] The preparation method of the sodium solid electrolyte material provided by the present invention adopts a traditional solid-phase preparation process, including batching, primary ball milling, drying, pre-burning (primary sintering), secondary ball milling, tableting, sintering (secondary sintering) and other steps. The process is simple, the raw materials are easy to obtain, and it is conducive to industrial production.

[0033] In a third aspect, the present invention provides an application of the above-mentioned sodium solid electrolyte material in a sodium ion battery.

[0034] Compared with the prior art, the present invention has the following beneficial effects:

[0035] The sodium solid electrolyte material provided by the present invention adjusts the Na ion concentration and channel size in the lattice by co-doping, promotes the formation of the Na5 phase, and has a high room temperature ionic conductivity and a low sintering temperature. Sodium and silicon are abundant elements in the earth's crust, the raw materials are easy to obtain, the cost is low, the preparation process is simple, and it has the advantage of being easy to industrialize. BRIEF DESCRIPTION OF THE DRAWINGS

[0036] Figure 1 The solid electrolyte Na prepared in Example 1 5.5 Ho 0.7 P 0.4 Si 3.6 O 12 X-ray diffraction pattern (XRD);

[0037] Figure 2 The solid electrolyte Na prepared in Example 1 5.5 Ho 0.7 P 0.4 Si 3.6 O 12 Scanning electron microscope (SEM) images of

[0038] Figure 3 The solid electrolyte Na prepared in Example 1 5.5 Ho 0.7 P 0.4 Si 3.6 O 12 Electrochemical impedance spectroscopy (EIS);

[0039] Figure 4 The solid electrolyte Na prepared in Example 2 5.3 Ho 0.8 P 0.3 Si 3.7 O 12 X-ray diffraction pattern (XRD);

[0040] Figure 5 The solid electrolyte Na prepared in Example 2 5.3 Ho 0.8 P 0.3 Si 3.7 O 12 Scanning electron microscope (SEM) images of

[0041] Figure 6 The solid electrolyte Na prepared in Example 2 5.3 Ho 0.8 P 0.3 Si 3.7 O 12 Electrochemical impedance spectroscopy (EIS);

[0042] Figure 7 The solid electrolyte Na prepared in Example 3 5.25 Ho 0.85 P 0.2 Si 3.8 O 12 X-ray diffraction pattern (XRD);

[0043] Figure 8 The solid electrolyte Na prepared in Example 3 5.25 Ho 0.85 P 0.2 Si 3.8 O 12 Scanning electron microscope (SEM) images of

[0044] Fig. 9 The solid electrolyte Na prepared in Example 35.25 Ho 0.85 P 0.2 Si 3.8 O 12 Electrochemical impedance spectroscopy (EIS);

[0045] Fig.10 The solid electrolyte Na prepared in Example 4 5.2 Ho 0.9 P 0.1 Si 3.9 O 12 X-ray diffraction pattern (XRD);

[0046] Fig.11 The solid electrolyte Na prepared in Example 4 5.2 Ho 0.9 P 0.1 Si 3.9 O 12 Scanning electron microscope (SEM) images of

[0047] Fig.12 The solid electrolyte Na prepared in Example 4 5.2 Ho 0.9 P 0.1 Si 3.9 O 12 Electrochemical impedance spectroscopy (EIS);

[0048] Fig.13 The solid electrolyte Na prepared in Example 5 5.1 Ho 0.95 P 0.05 Si 3.95 O 12 X-ray diffraction pattern (XRD);

[0049] Fig.14 The solid electrolyte Na prepared in Example 5 5.1 Ho 0.95 P 0.05 Si 3.95 O 12 Scanning electron microscope (SEM) images of

[0050] Fig.15 The solid electrolyte Na prepared in Example 5 5.1 Ho 0.95 P 0.05 Si 3.95 O 12 Electrochemical impedance spectroscopy (EIS);

[0051] Fig.16 The solid electrolyte Na prepared in Comparative Example 1 5 HoSi 4 O12 -950 X-ray diffraction spectrum (XRD);

[0052] Fig.17 The solid electrolyte Na prepared in Comparative Example 1 5 HoSi 4 O 12 -950 scanning electron microscope (SEM);

[0053] Fig.18 The solid electrolyte Na prepared in Comparative Example 1 5 HoSi 4 O 12 -Electrochemical impedance spectroscopy (EIS) at 950°C;

[0054] Fig.19 The solid electrolyte Na prepared in Comparative Example 2 5 HoSi 4 O 12 -1100 X-ray diffraction spectrum (XRD);

[0055] Fig. 20 The solid electrolyte Na prepared in Comparative Example 2 5 HoSi 4 O 12 -1100 scanning electron microscope (SEM);

[0056] Fig.21 The solid electrolyte Na prepared in Comparative Example 2 5 HoSi 4 O 12 -1100 electrochemical impedance spectroscopy (EIS);

[0057] Fig. 22 The solid electrolyte Na prepared in Comparative Example 3 4.5 HoP 0.8 Si 3.2 O 12 X-ray diffraction pattern (XRD);

[0058] Fig.23 The solid electrolyte Na prepared in Comparative Example 3 4.5 HoP 0.8 Si 3.2 O 12 Electrochemical impedance spectroscopy (EIS);

[0059] Fig.24 The solid electrolyte Na prepared in Comparative Example 4 6.2 Ho 0.6 Si 4 O 12 X-ray diffraction pattern (XRD);

[0060] Fig.25 The solid electrolyte Na prepared in Comparative Example 4 6.2 Ho 0.6 Si 4 O 12 Electrochemical impedance spectroscopy (EIS);

[0061] Fig.26 The solid electrolyte Na prepared in Comparative Example 5 5.25 Sc 0.85 P 0.2 Si 3.8 O 12 X-ray diffraction pattern (XRD);

[0062] Fig. 27 The solid electrolyte Na prepared in Comparative Example 5 5.25 Sc 0.85 P 0.2 Si 3.8 O 12 Electrochemical impedance spectroscopy (EIS);

[0063] Fig.28 This is a rate performance diagram of a full battery assembled using the solid electrolyte prepared in Example 3;

[0064] Fig.29 The charge and discharge specific capacity-voltage curves at different rates of a full battery assembled using the solid electrolyte prepared in Example 3;

[0065] Fig.30 This is a long cycle performance diagram of a full battery assembled using the solid electrolyte prepared in Example 3 at 1C. DETAILED DESCRIPTION

[0066] In order to better illustrate the purpose, technical scheme and advantages of the present invention, the present invention will be further described below in conjunction with specific examples. The test methods used in the following examples are conventional methods unless otherwise specified; the materials and reagents used are reagents and materials that can be obtained from commercial channels unless otherwise specified.

[0067] Example 1

[0068] An embodiment of the sodium solid electrolyte material of the present invention.

[0069] The sodium solid electrolyte material described in this embodiment is Na 5.5 Ho 0.7 P 0.4 Si 3.6 O 12 , and its preparation method is as follows:

[0070] (1) Put Na 2 CO3 、Ho 2 O 3 、SiO 2 and NH 4 H 2 PO 4 The raw materials were weighed according to the molar ratio determined by the chemical formula, and were mixed by ball milling at 650 rpm for 1 h, with a ball-to-material ratio of 30:1, and then dried at 100°C for 1 hour to obtain a raw material mixture powder;

[0071] (2) pre-calcining the raw material mixture powder at 600° C. for 24 hours to obtain a precursor powder;

[0072] (3) The precursor powder was ball-milled for a second time by dry milling, using a planetary ball mill at 300 rpm for 12 h with a ball-to-material ratio of 20:1 to obtain a uniformly refined powder, and then the powder was pressed at a pressure of 8 tons for 20 s to obtain an electrolyte green body with a diameter of 13 mm;

[0073] (4) The electrolyte green body is buried in the mother powder, sintered at 950° C. for 48 h, and naturally cooled to room temperature to obtain the Na 5.5 Ho 0.7 P 0.4 Si 3.6 O 12 Dense ceramic pieces.

[0074] The Na prepared in this example 5.5 Ho 0.7 P 0.4 Si 3.6 O 12 XRD of solid electrolytes Figure 1 ;

[0075] The Na prepared in this example 5.5 Ho 0.7 P 0.4 Si 3.6 O 12 The scanning electron microscope (SEM) image of Figure 2 .

[0076] Example 2

[0077] An embodiment of the sodium solid electrolyte material of the present invention.

[0078] The sodium solid electrolyte material described in this embodiment is Na 5.3 Ho 0.8 P 0.3 Si 3.7 O 12 , and its preparation method is as follows:

[0079] (1) Put Na 2 CO3 、Ho 2 O 3 、SiO 2 and NH 4 H 2 PO 4 Weigh the mixture according to the molar ratio determined by the chemical formula, use a planetary ball mill at 550 rpm for 2 h to mix, with a ball-to-material ratio of 25:1, and then dry at 60°C for 12 h to obtain a raw material mixture powder;

[0080] (2) pre-calcining the raw material mixture powder at 700° C. for 18 hours to obtain a precursor powder;

[0081] (3) The precursor powder was ball-milled for a second time by dry milling, using a planetary ball mill at 400 rpm for 6 h with a ball-to-material ratio of 15:1 to obtain a uniformly refined powder, and then the powder was pressed at a pressure of 6 tons for 20 s to obtain an electrolyte green body with a diameter of 13 mm;

[0082] (4) The electrolyte green body is buried in the mother powder, sintered at 1000° C. for 36 h, and naturally cooled to room temperature to obtain the Na 5.3 Ho 0.8 P 0.3 Si 3.7 O 12 Dense ceramic pieces.

[0083] The Na prepared in this example 5.3 Ho 0.8 P 0.3 Si 3.7 O 12 XRD of solid electrolytes Figure 4 ;

[0084] The Na prepared in this example 5.3 Ho 0.8 P 0.3 Si 3.7 O 12 The scanning electron microscope (SEM) image of Figure 5 .

[0085] Example 3

[0086] An embodiment of the sodium solid electrolyte material of the present invention.

[0087] The sodium solid electrolyte material described in this embodiment is Na 5.25 Ho 0.85 P 0.2 Si 3.8 O 12 , and its preparation method is as follows:

[0088] (1) Put Na 2 CO3 、Ho 2 O 3 、SiO 2 and NH 4 H 2 PO 4 Weigh the raw materials according to the molar ratio determined by the chemical formula, use a planetary ball mill at 450 rpm for 6 hours to mix, the ball-to-material ratio is 20:1, and then dry at 80°C for 4 hours to obtain a raw material mixture powder;

[0089] (2) pre-calcining the raw material mixture powder at 800° C. for 12 hours to obtain a precursor powder;

[0090] (3) The precursor powder was ball-milled for a second time by dry milling, using a planetary ball mill at 250 rpm for 18 h with a ball-to-material ratio of 10:1 to obtain a uniformly refined powder, and then the powder was pressed at a pressure of 6 tons for 20 s to obtain an electrolyte green body with a diameter of 13 mm;

[0091] (4) The electrolyte green body is buried in the mother powder, sintered at 1050° C. for 24 h, and naturally cooled to room temperature to obtain the Na 5.25 Ho 0.85 P 0.2 Si 3.8 O 12 Dense ceramic pieces.

[0092] The Na prepared in this example 5.25 Ho 0.85 P 0.2 Si 3.8 O 12 XRD of solid electrolytes Figure 7 ;

[0093] The Na prepared in this example 5.25 Ho 0.85 P 0.2 Si 3.8 O 12 The scanning electron microscope (SEM) image of Figure 8 .

[0094] Example 4

[0095] An embodiment of the sodium solid electrolyte material of the present invention.

[0096] The sodium solid electrolyte material described in this embodiment is Na 5.2 Ho 0.9 P 0.1 Si 3.9 O 12 , and its preparation method is as follows:

[0097] (1) Put Na 2 CO3 、Ho 2 O 3 、SiO 2 and NH 4 H 2 PO 4 Weigh the mixture according to the molar ratio determined by the chemical formula, use a planetary ball mill at 350 rpm for 12 hours to mix, the ball-to-material ratio is 15:1, and then dry at 90°C for 2 hours to obtain a raw material mixture powder;

[0098] (2) pre-calcining the raw material mixture powder at 900° C. for 6 hours to obtain a precursor powder;

[0099] (3) The precursor powder was ball-milled for a second time by dry milling, using a planetary ball mill at 200 rpm for 9 h with a ball-to-material ratio of 15:1 to obtain a uniformly refined powder, and then the powder was pressed at a pressure of 10 tons for 10 s to obtain an electrolyte green body with a diameter of 13 mm;

[0100] (4) The electrolyte green body is buried in the mother powder, sintered at 1100° C. for 12 h, and naturally cooled to room temperature to obtain the Na 5.2 Ho 0.9 P 0.1 Si 3.9 O 12 Dense ceramic pieces.

[0101] The Na prepared in this example 5.2 Ho 0.9 P 0.1 Si 3.9 O 12 XRD of solid electrolytes Fig.10 ;

[0102] The Na prepared in this example 5.2 Ho 0.9 P 0.1 Si 3.9 O 12 The scanning electron microscope (SEM) image of Fig.11 .

[0103] Example 5

[0104] An embodiment of the sodium solid electrolyte material of the present invention.

[0105] The sodium solid electrolyte material described in this embodiment is Na 5.1 Ho 0.95 P 0.05 Si 3.95 O 12 , and its preparation method is as follows:

[0106] (1) Put Na 2 CO3 、Ho 2 O 3 、SiO 2 and NH 4 H 2 PO 4 Weigh the mixture according to the molar ratio determined by the chemical formula, use a planetary ball mill at 250 rpm for 24 hours to mix, the ball-to-material ratio is 10:1, and then dry at 50°C for 24 hours to obtain a raw material mixture powder;

[0107] (2) pre-calcining the raw material mixture powder at 950° C. for 1 hour to obtain a precursor powder;

[0108] (3) The precursor powder was ball-milled for a second time by dry milling, using a planetary ball mill at 200 rpm for 12 h with a ball-to-material ratio of 10:1 to obtain a uniformly refined powder, and then the powder was pressed at a pressure of 4 tons for 30 s to obtain an electrolyte green body with a diameter of 13 mm;

[0109] (4) The electrolyte green body is buried in the mother powder, sintered at 1150° C. for 9 h, and naturally cooled to room temperature to obtain the Na 5.1 Ho 0.95 P 0.05 Si 3.95 O 12 Dense ceramic pieces.

[0110] The Na prepared in this example 5.1 Ho 0.95 P 0.05 Si 3.95 O 12 XRD of solid electrolytes Fig.13 ;

[0111] The Na prepared in this example 5.1 Ho 0.95 P 0.05 Si 3.95 O 12 The scanning electron microscope (SEM) image of Fig.14 .

[0112] Example 6

[0113] An embodiment of the sodium solid electrolyte material of the present invention.

[0114] The sodium solid electrolyte material described in this embodiment is Na 5.4 Nd 0.7 P 0.5 Si 3.5 O 12 , and its preparation method is as follows:

[0115] (1) Put Na 2 CO3 、Nd 2 O 3 、SiO 2 and NH 4 H 2 PO 4 Weigh the raw materials according to the molar ratio determined by the chemical formula, use a planetary ball mill at 450 rpm for 6 hours to mix, the ball-to-material ratio is 20:1, and then dry at 80°C for 4 hours to obtain a raw material mixture powder;

[0116] (2) pre-calcining the raw material mixture powder at 800° C. for 12 hours to obtain a precursor powder;

[0117] (3) The precursor powder was ball-milled for a second time by dry milling, using a planetary ball mill at 250 rpm for 18 h with a ball-to-material ratio of 10:1 to obtain a uniformly refined powder, and then the powder was pressed at a pressure of 6 tons for 20 s to obtain an electrolyte green body with a diameter of 13 mm;

[0118] (4) The electrolyte green body is buried in the mother powder, sintered at 950° C. for 24 h, and naturally cooled to room temperature to obtain the Na 5.4 Nd 0.7 P 0.5 Si 3.5 O 12 Dense ceramic pieces.

[0119] Comparative Example 1

[0120] The sodium solid electrolyte material in this comparative example is Na 5 HoSi 4 O 12 , (in order to distinguish it from Comparative Example 2, it is named Na 5 HoSi 4 O 12 -950) and its preparation method is as follows:

[0121] (1) Put Na 2 CO 3 、Ho 2 O 3 and SiO 2 Weigh the mixture according to the molar ratio determined by the chemical formula, use a planetary ball mill at 350 rpm for 12 hours to mix, the ball-to-material ratio is 15:1, and then dry at 90°C for 2 hours to obtain a raw material mixture powder;

[0122] (2) pre-calcining the raw material mixture powder at 900° C. for 6 hours to obtain a precursor powder;

[0123] (3) The precursor powder was ball-milled for a second time by dry milling, using a planetary ball mill at 200 rpm for 9 h with a ball-to-material ratio of 15:1 to obtain a uniformly refined powder, and then the powder was pressed at a pressure of 10 tons for 10 s to obtain an electrolyte green body with a diameter of 13 mm;

[0124] (4) The electrolyte green body is buried in the mother powder, sintered at 950° C. for 48 h, and naturally cooled to room temperature to obtain the Na 5 HoSi 4 O 12 -950 dense ceramic sheet.

[0125] The prepared Na 5 HoSi 4 O 12 -950 solid electrolyte XRD Fig.16 ;

[0126] The prepared Na 5 HoSi 4 O 12 -950 scanning electron microscope (SEM) Fig.17 .

[0127] Comparative Example 2

[0128] Solid electrolyte Na 5 HoSi 4 O 12 (In order to distinguish it from Comparative Example 1, it is named Na 5 HoSi 4 O 12 -1100), and its preparation method is as follows:

[0129] (1) Put Na 2 CO 3 、Ho 2 O 3 and SiO 2 Weigh the mixture according to the molar ratio determined by the chemical formula, use a planetary ball mill at 350 rpm for 12 hours to mix, the ball-to-material ratio is 15:1, and then dry at 90°C for 2 hours to obtain a raw material mixture powder;

[0130] (2) pre-calcining the raw material mixture powder at 900° C. for 6 hours to obtain a precursor powder;

[0131] (3) The precursor powder was ball-milled for a second time by dry milling, using a planetary ball mill at 200 rpm for 9 h with a ball-to-material ratio of 15:1 to obtain a uniformly refined powder, and then the powder was pressed at a pressure of 10 tons for 10 s to obtain an electrolyte green body with a diameter of 13 mm;

[0132] (4) The electrolyte green body is buried in the mother powder, sintered at 1100° C. for 12 h, and naturally cooled to room temperature to obtain the Na 5 HoSi 4 O 12 -1100 ceramic pieces.

[0133] The prepared Na 5 HoSi 4 O 12 -1100 solid electrolyte XRD Fig.19 ;

[0134] The prepared Na 5 HoSi 4 O 12 -1100 scanning electron microscope (SEM) Fig. 20 .

[0135] Comparative Example 3

[0136] The sodium solid electrolyte material in this comparative example is Na 4.5 HoP 0.8 Si 3.2 O 12 , and its preparation method is as follows:

[0137] (1) Put Na 2 CO 3 、Ho 2 O 3 、SiO 2 and NH 4 H 2 PO 4 Weigh the mixture according to the molar ratio determined by the chemical formula, use a planetary ball mill at 350 rpm for 12 hours to mix, the ball-to-material ratio is 15:1, and then dry at 90°C for 2 hours to obtain a raw material mixture powder;

[0138] (2) pre-calcining the raw material mixture powder at 900° C. for 6 hours to obtain a precursor powder;

[0139] (3) The precursor powder was ball-milled for a second time by dry milling, using a planetary ball mill at 200 rpm for 9 h with a ball-to-material ratio of 15:1 to obtain a uniformly refined powder, and then the powder was pressed at a pressure of 10 tons for 10 s to obtain an electrolyte green body with a diameter of 13 mm;

[0140] (4) The electrolyte green body is buried in the mother powder, sintered at 1100° C. for 12 h, and naturally cooled to room temperature to obtain the Na 4.5 HoP 0.8 Si 3.2 O 12 of ceramic pieces.

[0141] The prepared Na 4.5 HoP 0.8 Si 3.2 O 12 XRD of solid electrolytes Fig. 22 .

[0142] Comparative Example 4

[0143] The sodium solid electrolyte material in this comparative example is Na 6.2 Ho 0.6 Si 4 O 12 , and its preparation method is as follows:

[0144] (1) Put Na 2 CO 3 、Ho 2 O 3 and SiO 2 Weigh the mixture according to the molar ratio determined by the chemical formula, use a planetary ball mill at 350 rpm for 12 hours to mix, the ball-to-material ratio is 15:1, and then dry at 90°C for 2 hours to obtain a raw material mixture powder;

[0145] (2) pre-calcining the raw material mixture powder at 900° C. for 6 hours to obtain a precursor powder;

[0146] (3) The precursor powder was ball-milled for a second time by dry milling, using a planetary ball mill at 200 rpm for 9 h with a ball-to-material ratio of 15:1 to obtain a uniformly refined powder, and then the powder was pressed at a pressure of 10 tons for 10 s to obtain an electrolyte green body with a diameter of 13 mm;

[0147] (4) The electrolyte green body is buried in the mother powder, sintered at 1100° C. for 12 h, and naturally cooled to room temperature to obtain the Na 6.2 Ho 0.6 Si 4 O 12 of ceramic pieces.

[0148] The prepared Na 6.2 Ho 0.6 Si 4 O 12 XRD of solid electrolytes Fig.24 .

[0149] Comparative Example 5

[0150] The difference between Comparative Example 5 and Example 3 is that Sc 2 O 3 Replacement of Ho in raw materials 2 O 3 , the chemical formula is Na 5.25 Sc 0.85 P0.2 Si 3.8 O 12 Solid electrolyte ceramic sheet.

[0151] The prepared Na 5.25 Sc 0.85 P 0.2 Si 3.8 O 12 XRD of solid electrolytes Fig.26 .

[0152] Effect Example 1

[0153] In order to explore the ionic conductivity of the sodium solid electrolyte material obtained in the present invention, the upper and lower surfaces of the solid electrolyte ceramic sheets prepared in the embodiments and comparative examples were gold-sputtered using an ion sputtering gold-spraying instrument, and then an impedance test was performed, and the ionic conductivity thereof was calculated.

[0154] The electrochemical impedance spectroscopy results of the sodium solid electrolyte materials of Examples 1-5 of the present invention are respectively as follows Figure 3 , 6 , 9, 12, and 15, the electrochemical impedance spectroscopy results of the solid electrolytes of Comparative Examples 1-5 are shown as follows: Fig.18 , 21 , 23, 25, and 27. The ionic conductivity of the solid electrolytes in all embodiments and comparative examples is summarized in Table 1. In the embodiments, Na 5.5 Ho 0.7 P 0.4 Si 3.6 O 12 The ionic conductivity is 1.4×10 -3 S / cm、Na 5.3 Ho 0.8 P 0.3 Si 3.7 O 12 The ionic conductivity is 1.6×10 -3 S / cm、Na 5.25 Ho 0.85 P 0.2 Si 3.8 O 12 The ionic conductivity is 2.2×10 -3 S / cm、Na 5.2 Ho 0.9 P 0.1 Si 3.9 O 12 The ionic conductivity is 1.7×10 -3 S / cm、Na 5.1 Ho 0.95 P 0.05 Si 3.95 O 12The ionic conductivity is 1.5×10 -3 S / cm、Na 5.4 Nd 0.7 P 0.5 Si 3.5 O 12 The ionic conductivity is 2.5×10 -3 S / cm. In the comparative example, Na 5 HoSi 4 O 12 The ionic conductivity of -950 is 2.3×10 -4 S / cm、Na 5 HoSi 4 O 12 The ionic conductivity of -1100 is 5.7×10 -4 S / cm、Na 4.5 HoP 0.8 Si 3.2 O 12 The ionic conductivity is 2.1×10 -7 S / cm、Na 6.2 Ho 0.6 Si 4 O 12 The ionic conductivity is 9.9×10 -7 S / cm、Na 5.25 Sc 0.85 P 0.2 Si 3.8 O 12 The ionic conductivity is 2.5×10 -5 S / cm.

[0155] From the above conductivity results, we can know that:

[0156] (1) After reasonable co-doping modification within the scope of the present invention, the Na ion concentration and channel size in the lattice can be adjusted to obtain a solid electrolyte with a Na5 phase, and the conductivity is improved to a certain extent. From the comparison of Examples 1, 2, 3, 4, 5 and Comparative Examples 1 and 2, it can be seen that: in Comparative Examples 1 and 2 without P element doping, Comparative Example 1 cannot achieve material densification under low sintering temperature conditions, and the conductivity is significantly affected; in contrast, Examples 1, 2, 3, 4, and 5 doped with P elements within a limited range can reduce the densification sintering temperature, improve the conductivity, and improve the performance of the solid electrolyte. After adjusting the sodium ion concentration in the lattice by changing the ratio of Ho and P, the conductivity can be significantly improved, and the conductivity of Example 3 reaches 2.2mS / cm.

[0157] (2) From the comparison of Examples 1, 2, 3, 4, 5 and Comparative Example 3, it can be seen that excessive doping of P element will lead to the formation of Na3 impurity phase and a significant decrease in conductivity; from the comparison of Examples 1, 2, 3, 4, 5 and Comparative Example 4, it can be seen that when no P element is doped and the Ho ratio is low, it will lead to the formation of Na9 impurity phase and the conductivity will also be significantly reduced.

[0158] (3) From the comparison between Example 3 and Comparative Example 5, it can be seen that the solid electrolyte with Na5 structure can also be prepared by using rare earth atom Sc as structural atom, but the conductivity is relatively low, only 2.5×10 -5 S / cm. Ho element has a large ionic radius. Selecting it as a structural atom can adjust the lattice constant and the size of the Na ion channel, thereby obtaining a solid electrolyte material with high conductivity. Table 1 Summary of ionic conductivity of solid electrolytes in Examples and Comparative Examples

[0159] Chemical formula Conductivity (S / cm) Example 1 <![CDATA[Na 5.5 I have 0.7 P 0.4 Yes 3.6 OR 12 ]]> <![CDATA[1.4×10 -3 ]]> Example 2 <![CDATA[Na 5.3 I have 0.8 P 0.3 Yes 3.7 OR 12 ]]> <![CDATA[1.6×10 -3 ]]> Example 3 <![CDATA[Na 5.25 I have 0.85 P 0.2 Yes 3.8 OR 12 ]]> <![CDATA[2.2×10 -3 ]]> Example 4 <![CDATA[Na 5.2 I have 0.9 P 0.1 Yes 3.9 OR 12 ]]> <![CDATA[1.7×10 -3 ]]> Example 5 <![CDATA[Na 5.1 I have 0.95 P 0.05 Yes 3.95 OR 12 ]]> <![CDATA[1.5×10 -3 ]]> Example 6 <![CDATA[Na 5.4 Nd 0.7 P 0.5 From 3.5 Oh 12 ]]> <![CDATA[2.5×10 -3 ]]> Comparative Example 1 <![CDATA[Na 5 HoSi 4 O 12 -950]]> <![CDATA[2.3×10 -4 ]]> Comparative Example 2 <![CDATA[Na 5 HoSi 4 O 12 -1100]]> <![CDATA[5.7×10 -4 ]]> Comparative Example 3 <![CDATA[Na 4.5 HoP 0.8 Si 3.2 O 12 ]]> <![CDATA[2.1×10 -7 ]]> Comparative Example 4 <![CDATA[Na 6.2 I have 0.6 Yes 4 OR 12 ]]> <![CDATA[9.9×10 -7 ]]> Comparative Example 5 <![CDATA[Na 5.25 Sc 0.85 Q 0.2 Si 3.8 O 12 ]]> <![CDATA[2.5×10 -5 ]]>

[0160] Effect Example 2

[0161] In order to explore the application of the modified solid electrolyte provided by the present invention in sodium ion batteries, a full battery was assembled using the sodium solid electrolyte material of Example 3 for testing. Metal Na was attached to the negative electrode side, sodium vanadium phosphate was used as the positive electrode, and 10 μL NaClO was added to its interface. 4 Electrolyte increases contact.

[0162] The rate performance and specific capacity voltage curves of the full battery assembled with the sodium solid electrolyte material of Example 3 at 0.1C, 0.2C, 0.5C, 1C, and 2C are as follows: Fig.28 , 29 As shown; 1C long cycle performance results are as follows Fig.30 As shown: the first cycle discharge specific capacity is 111.5 mAh / g, and the capacity retention rate after 570 cycles is 94.7%, which indicates that the sodium solid electrolyte material prepared in the embodiment of the present invention can be applied to a full battery, and has good rate performance and long cycle performance.

[0163] Finally, it should be noted that the above embodiments are only used to illustrate the technical solution of the present invention rather than to limit the scope of protection of the present invention. Although the present invention has been described in detail with reference to the preferred embodiments, those skilled in the art should understand that the technical solution of the present invention can be modified or replaced by equivalents without departing from the essence and scope of the technical solution of the present invention.

Claims

1. A sodium solid electrolyte material and a preparation method and application thereof, characterized in that: The chemical formula of the sodium solid electrolyte material is Na 5+3x-y R 1-x P y Si 4-y O 12 , wherein R is at least one of Tm, Ho, Nd, Ce, and La, 0≤x<0.4, 0<y<0.

8.

2. The sodium solid electrolyte material according to claim 1, wherein R is preferably Ho or Nd. 3 . The sodium solid electrolyte material according to claim 1 , wherein preferably, 0≤x≤0.3, 0<y≤0.

5.

4. The sodium solid electrolyte material according to claim 1, characterized in that The electrical conductivity of the sodium solid electrolyte material is ≥1 mS / cm.

5. The method for preparing a sodium solid electrolyte material according to any one of claims 1 to 4, characterized in that: The following steps are involved: (1) ball milling and mixing a Na source, an R source, a Si source, and a P source to obtain a raw material mixture; (2) sintering the raw material mixture once to obtain a primary product; (3) performing secondary ball milling and tableting on the primary product to obtain an electrolyte green body; (4) performing secondary sintering on the electrolyte green body to obtain the sodium solid electrolyte material.

6. The method for preparing a sodium solid electrolyte material according to claim 5, characterized in that: The rotation speed of the first ball milling and the second ball milling is 200-800 rpm, and the time is 0.5-24 hours.

7. The method for preparing a sodium solid electrolyte material according to claim 5, characterized in that: In the step (2), the primary sintering temperature is 600-950° C., and the sintering time is 1-24 hours.

8. The method for preparing a sodium solid electrolyte material according to claim 5, characterized in that: In the step (3), the tabletting pressure is 2-15 tons.

9. The method for preparing a sodium solid electrolyte material according to claim 5, characterized in that: In the step (4), the secondary sintering temperature is 900-1150° C., and the sintering time is 1-48 hours.

10. Use of the sodium solid electrolyte material according to any one of claims 1 to 4 in a sodium ion battery.

Citation Information

Cited By

  • Sodium ion composite solid electrolyte material and preparation method and application thereof

    CN119994161A